Clinical utility of Dual Energy Computed Tomography in gout: current concepts and applications - Carotti, Marina; Salaffi, Fausto; Filippucci, Emilio; Aringhieri, Giacomo; Bruno, Federico; Giovine, Sabrina; Gentili, Francesco; Floridi, Chiara; Borgheresi, Alessandra; De Filippo, Massimo; Masciocchi, Carlo; Barile, Antonio; et al. (Acta Biomedica Atenei Parmensis, 2020)
Gout is the most common inflammatory arthritis and is increasing in prevalence and incidence in many countries worldwide. Dual Energy Computed Tomography (DECT) has a high diagnostic accuracy in established gout, but its diagnostic sensitivity is low in subjects with recent-onset gout. A meta-analysis of 17 studies showed a pooled sensitivity and specificity of 0.85 and 0.88, respectively. DECT is a useful diagnostic tool for patients with contraindications for joint aspiration or for those who refuse joint aspiration. This article aims to give an up to date review and summary of existing literature on the role and accuracy of DECT in the imaging of gout.